A Scoping Review of Indicators for Sustainable Healthy Diets - Harrison, Megan R.; Palma, Giulia; Buendia, Tomás; Bueno-Tarodo, Marta; Quell, Daria; Hachem, Fatima (Frontiers in Sustainable Food Systems, 2022)
Introduction: Diets are currently unsustainable in many countries as evidenced by the growing burden of malnutrition, degradation of natural resources, contributions to climate change, and unaffordability of healthy diets. Agreement on what constitutes a healthy and sustainable diet has been debated. In 2019, FAO and WHO published the Sustainable Healthy Diets Guiding Principles, defining what qualifies as a sustainable healthy diet. While valuable, these principles require measurable indicators to support their operationalization. Our scoping review aims to describe how sustainable healthy diets have been assessed in the literature since 2010. Methods: A search for English-language articles published in peer-reviewed journals was conducted from January 2010 through February 2020 across three databases. Out of the 504 articles initially identified, 103 articles were included. Metadata were extracted from each article on: publication year, country of study, study aims, methods, main data sources, indicators used to assess sustainable healthy diets, reported indicator strengths or limitations, and main study findings. A qualitative content analysis identified major conceptual themes across indicators and their frequency of use. Findings: From the 103 empirical articles included in our review, 57.3% were published after 2017. Most studies were carried out in high-income countries (74%). Approximately 42% of the articles assessed the sustainability of diets using solely health and environmental indicators; less than 25% assessed the sustainability of diets across health, environmental, and sociocultural aspects of sustainability. We found a substantial number of unique indicators used for assessing health (n=82), environmental (n=117), and sociocultural (n=43) aspects of diets. These indicators covered concepts related to health outcomes, aspects of diet quality, natural resources, climate change, cultural acceptability, and cost of diets. The preponderance of indicators currently used in research likely poses challenges for stakeholders to identify the most appropriate measures. Conclusion: Robust indicators for sustainable healthy diets are critical for understanding trends, setting targets, and monitoring progress across national and sub-national levels. Our review highlights the geographical imbalance, the narrow focus on health and environmental aspects, and the lack of common measures used in research. Measures registries could provide the decision-support needed by stakeholders to aid in the indicator selection process.